Confronting potential food industry 'front groups': case study of the international food information Council's nutrition communications using the UCSF food industry documents archive - Sarah Steele; Lejla Sarcevic; Gary Ruskin; David Stuckler (BMC, 2022)
Abstract Background There are growing concerns that the public's trust in science is eroding, including concerns that vested interests are corrupting what we know about our food. We know the food industry funds third-party 'front groups' to advance its positions and profits. Here we ask whether this is the case with International Food Information Council (IFIC) and its associated Foundation, exploring its motivations and the potential for industry influence on communications around nutritional science. Method We systematically searched the University of California San Francisco's Food Industry Documents Archive, for all documents pertaining to IFIC, which were then thematically evaluated against a science-communication influence model. Results We identified 75 documents which evidence that prominent individuals with long careers in the food industry view IFIC as designed to: 1) advance industry public relations goals; 2) amplify the messages of industry-funded research organizations; and 3) place industry approved experts before the press and media, in ways that conceal industry input. We observed that there were in some cases efforts made to conceal and dilute industry links associated with IFIC from the public's view. Discussion Instances suggesting IFIC communicates content produced by industry, and other industry-funded organisations like ILSI, give rise to concerns about vested interests going undetected in its outputs. IFIC's deployment to take on so-called "hard-hitting issues" for industry, summating evidence, while countering evidence that industry opposes, give rise to concerns about IFIC's purported neutrality. IFIC's role in coordinating and placing industry allies in online and traditional press outlets, to overcome industry's global scientific, legislative, regulatory and public relations challenges, leads also to concerns about it thwarting effective public health and safety measures. Conclusions IFIC's promotion of evidence for the food industry should be interpreted as marketing strategy for those funders. Effective science communication may be obfuscated by undeclared conflicts of interests.